2019
DOI: 10.1177/0890334419845871
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Breastfeeding Among Women With Gestational Diabetes

Abstract: Background: Breastfeeding offers benefits to mother and child but is frequently not practiced among women whose pregnancy is complicated by gestational diabetes mellitus. Factors associated with not initiating or not maintaining breastfeeding among these women have been little investigated. Research aims: (1) To evaluate the frequency of breastfeeding for 30 days among women with a recent pregnancy complicated by gestational diabetes and (2) to determine factors associated with not initiating or not maintainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In line with previous studies, we found that non-smokers, higher educated, and married women had a longer duration of breastfeeding [20,37,39]. Some studies have shown that delivery complications, such as Caesarean section, or serious health problems of the newborn lead to lactation difficulties [19,20,38]. We did not observe such an influence.…”
Section: Gdm = Gestational Diabetes Mellitus; Hr = Hazard Ratiosupporting
confidence: 90%
See 1 more Smart Citation
“…In line with previous studies, we found that non-smokers, higher educated, and married women had a longer duration of breastfeeding [20,37,39]. Some studies have shown that delivery complications, such as Caesarean section, or serious health problems of the newborn lead to lactation difficulties [19,20,38]. We did not observe such an influence.…”
Section: Gdm = Gestational Diabetes Mellitus; Hr = Hazard Ratiosupporting
confidence: 90%
“…Lactation difficulties among women with GDM are at least partly explained by their higher likelihood of obesity and delivery complications, including cesarean section, compared women without Gestational diabetes mellitus [18,19]. Further, neonates of women with GDM seem to have an increased risk for both low birthweight and macrosomia as well as admissions to neonatal intensive care unit, all of which may have a detrimental influence on breastfeeding [20,21]. Most previous data originate from study cohorts consisting of both primiparous and multiparous women.…”
Section: Introductionmentioning
confidence: 99%
“…The independent variables included the sociodemographic data, which showed correlations with the breastfeeding self-efficacy scale in the literature [ 1 , 13 , 26 ], such as age, BMI, level of education, mother’s occupation, husband’s monthly income, place of residence, smoking status, and chronic diseases other than GDM parity status. Other factors that showed correlations in the literature were included [ 9 , 13 , 21 , 22 , 27 ] such as previous breastfeeding experience, satisfaction with previous breastfeeding experience, previous breastfeeding duration, inquiry about the intention to breastfeed the coming newborn, and health education sources.…”
Section: Methodsmentioning
confidence: 99%
“…Research has demonstrated that various factors can lead to barriers to successful breastfeeding. One of these factors is gestational diabetes mellitus (GDM) [ 1 ], which is defined as “the type of glucose intolerance that develops in the second and third trimester of pregnancy, resulting in hyperglycemia of variable severity” [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, according to a study conducted in Japan [ 10 ], the breastfeeding rate among women with GDM is lower than that of women without GDM. There are many factors that influence the initiation and continuation of women’s breastfeeding [ 11 ]. However, according to Rollins et al [ 12 ], the health system and services are among the main factors associated with the status of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%